Optimizing Government Policies On Profession Zakat - Nur Mohamad Kasim (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
The significant potential of zakat on profession needs to be actualized through a clear regulation. The targets of zakat on profession are: Ministry or State Institutions, Local Government, State-owned Enterprises, Local Government Owned Enterprises, even other professions that have a high income. The government's efforts to facilitate zakat on profession are solely aimed at making the mechanism of zakat management to be good, transparent and integrated into a system. However, zakat levies should have a specific rule that is binding all citizens, especially all Muslim Civil State Apparatus (henceforth called as ASN) who certainly meets the applicable regulations. For those who have income and already reach nishab or nominal income limit must pay zakat, while the ones whose incomes do not reach nishab are not obliged to do such a thing. Gorontalo province is one of the regions whose population is predominantly Muslim and has potential in terms of Islamic values-based economic development. Therefore, there needs to be a strict regulation to regulate zakat on profession, so that the utilization of zakat can help to alleviate the burden of the poor. By the existence of regulation, people who pay and receive zakat are equally having the benefits of zakat. This is to say that government has a prominent role and responsibility in optimizing the enactment of zakat on profession since the reality of the most significant zakat received by BAZNAS (Islamic board which oversees the collection of Zakat) in Gorontalo province is from ASN and other professions income.